Invasive cystic hypersecretory carcinoma of the breast: a rare variant of breast cancer: a case report and review of the literature - Jie Sun; Xing Wang; Cuifang Wang (BMC Cancer, 2019)
Abstract Background Cystic hypersecretory carcinoma is a rare subtype of breast cancer. It is a member of cystic hypersecretory lesions, which include a series of pathological disease lineages: cystic hypersecretory hyperplasia (CHH), CHH with atypia, cystic hypersecretory carcinoma (CHC) and invasive CHC. It was found that most cystic hypersecretion lesions were in situ carcinoma, and only 19 cases of invasive cystic hypersecretion carcinoma were reported. Case presentation We are reporting a case of a 63-year-old female who had a lump in her left breast for 3 years. A modified radical mastectomy was done and morphological diagnosis of invasive CHC with axillary node metastasis was made. Conclusions Owing to a smaller number of reported cases, little is known about the biological behavior, prognosis and molecular study of cystic hypersecretion lesions. Therefore, more cases with follow-up data are needed to reveal the biological behavior of this rare tumor.